The cGAS-STING Pathway Affects Vertebral Bone but Does Not Promote Intervertebral Disc Cell Senescence or Degeneration - Ottone, Olivia K.; Kim, C. James; Collins, John A.; Risbud, Makarand V. (Frontiers in Immunology, 2022)
The DNA-sensing cGAS-STING pathway promotes the senescence-associated secretory phenotype (SASP) and mediates type-I interferon inflammatory responses to foreign viral and bacterial DNA as well as self-DNA. Studies of the intervertebral disc in humans and mice demonstrate associations between aging, increased cell senescence, and disc degeneration. Herein we assessed the role of STING in SASP promotion in STING gain- (N153S) and loss-of-function mouse models. N153S mice evidenced elevated circulating levels of proinflammatory markers including IL-1b, IL-6, and TNF-a showed elevated monocyte and macrophage abundance in the vertebral marrow, and exhibited a mild trabecular and cortical bone phenotype in caudal vertebrae. Interestingly, despite systemic inflammation, the structural integrity of the disc and knee articular joint remained intact, and cells did not show a loss of their phenotype or elevated SASP. Transcriptomic analysis of N153S tissues demonstrated an upregulated immune response by disc cells, which did not closely resemble inflammatory changes in human tissues. Interestingly, STING-/- mice also showed a mild vertebral bone phenotype, but the absence of STING did not reduce the abundance of SASP markers or improve the age-associated disc phenotype. Overall, the analyses of N153S and STING-/- mice that the cGAS-STING pathway is not a major contributor to SASP induction and consequent disc aging and degeneration but may play a minor role in the maintenance of trabecular bone in the vertebrae. This work contributes to a growing body of work demonstrating that systemic inflammation is not a key driver of disc degeneration.